The Significance of Key E-Service Quality Dimensions Toward Customer Loyalty of Generation Y and Generation Z when Shopping Fashion Products Online at Shopee Indonesia with Customer Perceived Value as the Mediator - Monica Christy Setiawan (iBuss Management, 2020)
Nowadays, e-commerce has been growing rapidly in Indonesia. Online shopping has been done by many people with the increasing number of purchases every year. One of the top three e-commerce platform in Indonesia is Shopee, with the significant growth of the number of users. Shopee has been popular with fashion as the number one most purchased category. Moreover, the majority of the users are coming from generation Y and generation Z, the largest market of the current era. Therefore, the researcher wants to examine how significant the e-service quality of Shopee Indonesia as an online shopping platform in retaining the customers from both generations. The research will identify if the key e-service quality dimensions significantly affect the customer loyalty of each generation, and whether customer perceived value plays the role of mediator between the key e- service quality dimensions and customer loyalty for each generation. The research is conducted using multiple linear regression analysis, with the data gathered using simple random sampling method. Sobel test is also conducted to analyse the mediating variable. The statistical analysis is done using IBM SPSS program. The result of the research shows that for generation Y and generation Z, the key E-SERVQUAL dimensions except reliability, significantly affect customer loyalty with perceived value as the mediator, while reliability does not have any significant effect toward either perceived value or customer loyalty. Keywords: Key E-SERVQUAL Dimensions, Customer Perceived-Value, Customer Loyalty, Generation Y, Generation Z